2019
DOI: 10.1039/c9ra03151k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of 4-(1H-1,2,4-triazol-1-yl)benzoic acid hybrids as anticancer agents

Abstract: A series of 4-(1H-1,2,4-triazol-1-yl)benzoic acid hybrids (1–17) was successfully synthesized and their structures were established by NMR and MS analysis. Their anticancer activity against HCT-116, MCF-7 and normal human RPE-1 cells were examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Throughout our research, we have noticed that the 1,2,4-triazole or 1,2,3-triazole derivatives showed antioxidant properties [28][29][30][31][32][33][34][35] and demonstrated cytotoxic activity as well. In a previous work, the molecular hybridization technique was employed to incorporate the triazole unit with isothiocyanate and substituted benzylidene groups into a single molecule; the resulting targets have the potential to exhibit potent antiproliferative activity against HCT-116 and MCF-7 human cancer cell lines and showed very weak cytotoxicity against normal cells [35].…”
Section: Introductionmentioning
confidence: 79%
“…Throughout our research, we have noticed that the 1,2,4-triazole or 1,2,3-triazole derivatives showed antioxidant properties [28][29][30][31][32][33][34][35] and demonstrated cytotoxic activity as well. In a previous work, the molecular hybridization technique was employed to incorporate the triazole unit with isothiocyanate and substituted benzylidene groups into a single molecule; the resulting targets have the potential to exhibit potent antiproliferative activity against HCT-116 and MCF-7 human cancer cell lines and showed very weak cytotoxicity against normal cells [35].…”
Section: Introductionmentioning
confidence: 79%
“…Among the synthesized 4-(1 H -1,2,4-triazol-1-yl)benzoic acid hybrids 146 – 148 ( Fig. 33 ), compounds 148b (IC 50 : 15.6 μM) and 148c (IC 50 : 23.9 μM) displayed potent activity against MCF-7 and HCT-116 cancer cell lines, respectively when compared with doxorubicin (IC 50 : 19.7 and 22.6 μM, respectively) [ 134 ]. A mechanistic study illustrated that compounds 146b and 148b induced apoptosis in MCF-7 cells.…”
Section: Biological Activities Of 124-triazole Derivativesmentioning
confidence: 99%
“…The findings revealed apoptotic profile of melanoma cells after treatment with 1,2,4-triazole compounds for the first time. Apoptosis of some other cancers such as prostate, colon, breast and lung were induced by different 1,2,4-triazole derivative compounds [30][31][32]. 1,5-disubstituted 1,2,4-triazole compounds were shown to induce apoptosis and cell cycle arrest at the G 2 /M phase in cervix (HeLa) and leukemia (Jurkat) cancer cells [33].…”
Section: Int J Biol Chem (Online)mentioning
confidence: 99%